Expectant management versus multifetal pregnancy reduction in dichorionic triamniotic (DCTA) triplets: Single centre experience. (September 2021) - Shaw, C.J.; Paramasivam, G.; Vacca, C.; Lees, C.C.
Abstract: Objectives: In trichorionic triplet pregnancies, multifetal pregnancy reduction (MFPR) reduces the risk of preterm birth, neonatal morbidity and mortality without increasing miscarriage. A similar benefit has been suggested in dichorionic triamniotic (DCTA) pregnancy, but multiple methods are currently used. This study investigates if the method of reduction used in DCTA triplet pregnancy influences the evidence of benefit from MFPR. Methods: This is a retrospective cohort study of DCTA pregnancies between 2010 and 2019 who attended a single UK fetal medicine tertiary referral center. Cohorts were defined based on MFPR decision and method. The primary outcome was offspring survival until neonatal discharge. The secondary outcomes included miscarriage, preterm birth, livebirth, rates of small for gestational age (SGA) neonates, ans maternal morbidity. To evaluate the differences in neonatal survival until discharge we used Cox proportional regression to calculate hazard rates (HR) and 95% confidence intervals (CI). Differences in secondary outcomes were compared using univariate analysis. Results: The study reports the outcomes for 83 DCTA pregnancies. MFPR to DCDA twins was chosen in 19 pregnancies (14 radiofrequency ablation, RFA; 5 intrafetal laser, IFL); in 9 pregnancies selective reduction to a singleton was performed by KCl injection. The rate of pregnancies in with ≥ 1 fetus born alive was not different between groups (p = 0.90). However, the number of expected neonates alive at discharge from hospital was highest in the RFA group (89%, HR 0.28, 95% CI 0.21–0.87, p = 0.02). Rates of premature delivery before 32 weeks (p = 0.02), low birth weight (p < 0.001) and birthweight < 10th percentile (p = 0.01) were all elevated in the expectant management group, compared to women who opted for reduction. There was no difference in miscarriage between groups. Conclusions: Our study suggests that MFPR by RFA, an established and widely available procedure, is of benefit in promoting neonatal survival until discharge in DCTA triplets.